Wage determination in China during the reform period - Carsten A. Holz (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
The purpose of this paper is to ascertain how wages are being determined in China during the reform period. The paper focuses on the development of the regulatory framework since 1978 and proceeds by examining official regulations regarding labor market institutions and wage setting, and by evaluating their potential implications for actual wage setting.
URN:NBN:fi:bof-201408072220
Keywords: J30; J31; J41; J45; M52; M54; M55; P23; 330; wage determination; labor market institutions; minimum wages; wage classification system; wage level and structure; labor contracts; collective bargaining; public sector wages; wage-performance link